An Impact Of Service Quality Towards Customer Satisfaction In Pos Malaysia: The Mediating Role Of Self-Service Technologies - Tan, Siew Fang (2014)
An Impact of service quality (i.e. tangibles, reliability, assurance, empathy and responsiveness) towards customer satisfaction in Pos Malaysia with the mediating role of self-service technologies has been well recognized. To contribute knowledge to this underexplored postal service area, a study, based on the gap theory and diffusion of innovation theory approach, was conducted on this Pos Malaysia research. A self-administered questionnaire was designed to establish the scales. The research mainly focused on the state of Perlis, Kedah, Penang and northern area of Perak, the northern region of Malaysia.